The computer simulation of mixing of non-Newtonian fluid in 2-D semi-cylinder cavity - Stręk, Tomasz (Computer Assisted Methods in Engineering and Science, 2023)
In this paper some results of the computer simulation of mixing of non-Newtonian fluid are presented. Numerical calculations were done for dimensionless form of the equations of motion for the Carreau fluid in incompressible and viscous flow in a two-dimensional semi-cylindrical cavity. The full Navier- Stokes equations for the Carreau fluid were written in velocity- vorticity, and next in finite difference form. The solutions were accomplished by finite time-step advancement. The mixing process was studied by tracking the motion of particles in the mixing region. The particles were represented by marked points. The mixing efficiency was quantified in terms of the average distance between the tracer particles and the centroid of the particle distribution.